A study on the interpretation of spontaneous potential and resistivity logs in layered aquifer sequence of Pondicherry Region, South India - Thilagavathi, R.; Chidambaram, S.; Prasanna, Mohan Viswanathan; Pethaperumal, S. (Springer, 2014)
Geophysical logs provide a strong mechanism for interpretation and determination of the depositional environments, facies and also help in interpretations of hydrogeologic units. Spontaneous potential (SP) and resistivity logs can be used as an indicator of textural parameters. Pondicherry region has a complicated geology and with formation of different ages. The boreholes (BH) of this region are examined for litholog, SP and resistivity from four different BH locations, viz, Ariyankuppam, Chinnaverampattinam, Thavalakuppam and Nallavadu. These locations were studied and interpreted by using the shapes of the curves to identify the depositional environments, and this was later compared with the vertical litholog profile. Comparing the variation of these logs, the lateral variation of sedimentary facies was also attempted. The average resistivity values of Ariyankuppam, Chinnaverampattinam, Thavalakuppam and Nallavadu are 42.4, 30.4, 50.4 and 28.3 Ωm, respectively. Majority of the resistivity values corresponds from fine- to medium-grained sand, clayey pebbles, fine to very coarse sand and clayey sand with lignite. Frequency of resistivity values in each BH were identified for determining the dominant representative grain size. The study has pointed out the lithological variation of the system laterally and vertically using geophysical well logs.